Design and Optimization of the Dies for the Isothermal Forging of a Cam. (2015) - Salcedo, D.; Luis, C.J.; Luri, R.; León, J.; Puertas, I.; Fuertes, J.P.
Abstract: In the present study, the design of the dies required for the isothermal forging of a cam is analysed by finite volume method. Specifically, cams are of great importance in automotive industry, where a lower weight and an improvement in the lubrication or in the materials to be in contact lead to a significant reduction in the fuel cost. The flow stress curves of one Al-Mg alloy were firstly determined by using compression tests. Once these flow stress curves were obtained, FV simulation was employed. In the forging process, the optimum die configuration has been selected. To this end, several aspects have been taken into account such as the force required for the forging, the correct die filling, the introduced plastic strain and the damage imparted to the billet.